OPTIMALISASI PENGERINGAN RUMPUT LAUT MELALUI SOLAR DRYER TIPE GREEN HOUSE DI LANDU LEKO KABUPATEN ROTE NDAO - Lukas, Ade Yulita Hesti; Kangkan, Alexander L.; Suleman, Suleman; Manilapai, Jusuf R.; Sine, Kiik G. (Universitas Mataram, 2025)
This community service activity aims to optimize seaweed production through the application of greenhouse-type solar drying technology as an innovative and environmentally friendly solution. The community engagement method was carried out through a series of activities under the theme of “Education and Community Service,” which included counseling, discussions, and training on greenhouse construction. The activity took place on May 30–31, 2025, involving ten members of the Samudera Kasih seaweed farmer group as partners. The results showed that the use of greenhouse drying technology helped maintain cleanliness and reduced the moisture content of the seaweed, with cleanliness levels—measured by reduced dust and dirt contamination—increasing by 10% compared to conventional drying methods. However, the drying time remained similar to the conventional method because the system was not equipped with a special ventilator or heating/fan unit. The implementation of this technology also contributed to increased income and work efficiency among farmers, particularly during the rainy season. In conclusion, the greenhouse drying technology proved effective in supporting the sustainability of seaweed production in Rote Ndao Regency. However, it is recommended that the equipment be equipped with a ventilator to enhance its effectiveness.